A comparative socio-legal and maqasid analysis of waṣiyyah wājibah in Islamic inheritance law in Indonesia and Malaysia - Susanti, Neneng Desi; Arisman, Arisman; Kasnan, Kasnan; Mohd Ruslan, Ros Amira (Universitas Islam Indonesia, 2026)
IntroductionIslamic inheritance law is widely recognized for its doctrinal clarity, yet contemporary social transformations have exposed gaps between classical rules and modern family realities. The concept of waṣiyyah wājibah (compulsory bequest) has emerged as a legal mechanism to address the exclusion of socially dependent individuals such as adopted children, orphaned grandchildren, and interfaith relatives. Despite its growing importance, comparative and integrative studies examining its application across different legal systems remain limited.ObjectivesThis study aims to analyze the concept and implementation of waṣiyyah wājibah in Indonesia and Malaysia through a comparative framework. It seeks to identify the legal, institutional, and socio-cultural factors shaping its application, and to evaluate its legitimacy and function using sociological and maqāṣid al-sharīʿah perspectives.MethodThe research adopts a qualitative, doctrinal–comparative approach based on the analysis of legal texts, statutory regulations, judicial decisions, and scholarly literature. It integrates normative legal analysis with socio-legal interpretation and purposive reasoning to examine how waṣiyyah wājibah operates within different institutional contexts.ResultsThe findings reveal that waṣiyyah wājibah functions as a flexible instrument of legal adaptation in both countries, though with distinct characteristics. Indonesia demonstrates a more expansive and jurisprudence-driven model, where courts extend the scope of compulsory bequests to address diverse social realities. Malaysia, by contrast, exhibits a more structured and decentralized approach, shaped by state enactments and procedural frameworks. In both systems, waṣiyyah wājibah remains bounded by doctrinal constraints and justified through principles of justice, welfare, and the objectives of Islamic law.ImplicationsThe study highlights the role of waṣiyyah wājibah in enhancing family welfare, reducing inheritance disputes, and promoting socially responsive legal outcomes. It also underscores the importance of institutional design and judicial reasoning in shaping the effectiveness of Islamic legal reform.Originality/NoveltyThis study offers an integrated comparative analysis that combines doctrinal, socio-legal, and maqāṣid-based perspectives. It contributes to the literature by demonstrating how Islamic inheritance law can adapt to contemporary challenges while maintaining its normative foundations.